Erratum: A Behavioral Study of Promethazine Interaction with Analgesic Effect of Diclofenac: Pain Combination Therapy - Niloofar Amidi; Zohreh Izadidastenaei; Malihe Araghchian; Davoud Ahmadimoghaddam (Korean Pharmacopuncture Institute, 2021)
The aim of this study was to report on the improvement of shoulder pain resulting from disorders of the rotator cuff such as impingement syndrome and adhesive capsulitis, by manual acupuncture (MA) and pharmacopuncture (PA) following origin/insertion technique (OIT) of applied kinesiology (AK). Two patients were treated with MA and PA after OIT on shoulder muscles. The Numerical Rating Scale and the assessment of the Japanese Orthopedic Association scores were used to assess the pain, and ultrasound images were taken to compare treatment outcome. This study showed that MA and PA following OIT may be an effective treatment for impingement syndrome and adhesive capsulitis.